Hybrid femtosecond laser system on base of photochemically; Известия вузов. Физика; Т. 55, № 10, part 3 - Losev V. F. Valery Fedorovich; Alekseev S. V. Sergey Vladimirovich; Ivanov N. G.; Kovalchuk B. M. Boris Mikhailovich; Mesyats G. A. Gennady Andreyevich; Mikheev L. D.; Panchenko Yu. N.; Ratakhin N. A. Nikolay Aleksandrovich (2012, 2012)
Title screen